2020
DOI: 10.1111/cyt.12894
|View full text |Cite
|
Sign up to set email alerts
|

The role of breast fine needle aspiration during and post‐COVID‐19 pandemic: A fast and safe alternative to needle core biopsy

Abstract: Fine needle aspiration (FNA) may be used to study breast lesions in patients that do not have access to more complex procedures during the COVID‐19 pandemic. Furthermore, FNA can be a helpful screening method in the post‐pandemic era when a greater number of patients than usual with delayed treatment can overburden clinics and hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…The TCB has become one of the best methods in terms of reliability, accuracy, and reproducibility in the diagnosis of breast lesions. Pinto D. et al in their study, claimed that FNABs could be an accurate and valuable method in symptomatic breast lesions in the period of COVID-19 in terms of both being fast and requiring less personnel and less invasive 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The TCB has become one of the best methods in terms of reliability, accuracy, and reproducibility in the diagnosis of breast lesions. Pinto D. et al in their study, claimed that FNABs could be an accurate and valuable method in symptomatic breast lesions in the period of COVID-19 in terms of both being fast and requiring less personnel and less invasive 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Vigliar et al reported a relative increase in the percentage of breast nodule FNAs during the COVID‐19 pandemic compared to the same period in 2019 (11.7% and 3.7%, respectively; P = .002) 8 . FNAs showed important advantages compared to more invasive core needle biopsies 14 . In particular, in a period with a limited number of personnel, FNAs are more cost‐effective and quicker to perform than core needle biopsies 14 .…”
Section: The Effect Of Covid‐19 On Cytopathology Diagnostic Activitymentioning
confidence: 99%
“…FNAs showed important advantages compared to more invasive core needle biopsies 14 . In particular, in a period with a limited number of personnel, FNAs are more cost‐effective and quicker to perform than core needle biopsies 14 . In addition, cytological material is suitable for ancillary techniques 43 .…”
Section: The Effect Of Covid‐19 On Cytopathology Diagnostic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…At this moment, many countries around the world are in lockdown again; although the reduction in cases is less dramatic this time, ongoing constraints on health services overburdened by COVID‐19 will result in delays and increased waiting lists for vitally important diagnostic and therapeutic procedures. Cytopathology can play a role in alleviating the backlog of patients, providing a quick and cost‐effective diagnosis, as for example in breast fine needle aspiration 14 …”
mentioning
confidence: 99%